Application of Taguchi and ANOVA methods in the optimisation of a direct evaporative cooling pad. Issue 5 (3rd September 2021) - Laknizi, Azzeddine; Ben Abdellah, Abdellatif; Mahdaoui, Mustapha; Anoune, Kamal
ABSTRACT: The evaporative cooling pad system permits to cool buildings with less consumption of the electricity and without any use of refrigerant gases. A good evaporative cooling pad system must have a higher coefficient of performance and a lower rate of water consumption. In this study, the Taguchi method is used to investigate the effect of the velocity, the thickness of the pad, and the type of pads on the performances of cellulosic cooling pads. It was found that the velocity has more influence on the coefficient of performance and the water consumption while the pad thickness is the more significant parameter on the outlet temperature. For the three indicators, the best combinations of the influencing parameters are identified. The obtained results are confirmed by ANOVA analysis, and for fast sizing of the considered cooling pads, a regression model was presented for the aforementioned performance indicators.